IMPLEMENTASI PERMENDAGRI NOMOR 2 TAHUN 2016 TENTANG KARTU IDENTITAS ANAK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA DUMAI - Rizka Gusti Mirta; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this study is to describe and explain the implementation of the Child Identity Card Policy in Dumai City. and explain and describe what factors are the obstacles and impetus for the implementation of the Identity Card Policy in Dumai City. This research uses qualitative research. The required data are both primary data and secondary data obtained through observation, interviews and documentation and then analyzed based on research problems. The results of this study indicate that the implementation of the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards has been going well. Supporting the implementation of Permendagri Factor Number 2 of 2016 concerning Child Identity Cards, namely the existence of great motivation to maintain performance, then supported by community participation, developing human resources, and information technology that is able to support program implementation, while the obstacle is when there is interference network that causes the completion is not in accordance with the specified timeKeywords: Implementation, Minister of Home Affairs Regulation No. 2 of 2016, Child Identity Card